A randomized controlled trial of a faith-placed, lay health advisor delivered smoking cessation intervention for rural residents - Schoenberg, Nancy E. (Prev Med Rep, 2016)
INTRODUCTION: Rural US residents smoke at higher rates than urban or suburban residents. We report results from a community-based smoking cessation intervention in Appalachian Kentucky. STUDY DESIGN: Single-blind, group-randomized trial with outcome measurements at baseline, 17 weeks and 43 weeks. SETTING/PARTICIPANTS: This faith-placed CBPR project was located in six counties of rural Appalachian Kentucky. A total of 590 individual participants clustered in 28 churches were enrolled in the study. INTERVENTION: Local lay health advisors delivered the 12-week Cooper/Clayton Method to Stop Smoking program, leveraging sociocultural factors to improve the cultural salience of the program for Appalachian smokers. Participants met with an interventionist for one 90 min group session once per week incorporating didactic information, group discussion, and nicotine replacement therapy. MAIN OUTCOME MEASURES: The primary outcome was self-reported smoking status. Secondary outcomes included Fagerström nicotine dependence, self-efficacy, and decisional balance. RESULTS: With post-intervention data from 92% of participants, those in intervention group churches (N = 383) had 13.6 times higher odds of reporting quitting smoking one month post-intervention than participants in attention control group churches (N = 154, p < 0.0001). In addition, although only 3.2% of attention control group participants reported quitting during the control period, 15.4% of attention control participants reported quitting smoking after receiving the intervention. A significant dose effect of the 12-session Cooper/Clayton Method was detected: for each additional session completed, the odds of quitting smoking increased by 26%. CONCLUSIONS: The Cooper/Clayton Method, delivered in rural Appalachian churches by lay health advisors, has strong potential to reduce smoking rates and improve individuals' health.